2006
DOI: 10.1345/aph.1g717
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Medication Errors in Pediatric Patients

Abstract: Interpretation of the literature was hindered by variation in definitions employed by different researchers, varying research methods and setting, and a lack of theory-based research. Overall, it would appear that our initial concern about MEs in pediatrics has been validated; however, we do not know the actual size of the problem. Further work to determine the incidence and causes of MEs in pediatrics is urgently needed, as well as evaluation of the best interventions to reduce them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
165
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(188 citation statements)
references
References 43 publications
13
165
1
9
Order By: Relevance
“…This observation is consistent with published data on medication errors in pediatric patients. 13,14 Incorrect dosage errors in pediatric surgery are a well-recognized problem as the frequent need for weight-adjusted dosing makes these patients particularly susceptible to this type of error. Our findings support the relationship between the type of surgical case and the incidence of medication errors/pre-errors.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with published data on medication errors in pediatric patients. 13,14 Incorrect dosage errors in pediatric surgery are a well-recognized problem as the frequent need for weight-adjusted dosing makes these patients particularly susceptible to this type of error. Our findings support the relationship between the type of surgical case and the incidence of medication errors/pre-errors.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that 15% of prescribing error in pediatric was due to "tenfold error," and this happened during dose calculation and transaction while using different units (milligrams instead of micrograms). [4,5] Different pediatric population are associated with higher risk of prescribing error like ill patients admitted to pediatric intensive care unit (PICU) and neonatal ICU, patients provided prescription with illegible handwriting at ambulatory care services. Authors found that several environmental and personal factors might associate with the risk of prescribing error such as years of experience, fatigue, and workload.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy, antiepileptic, antimicrobials, and analgesics are considered the top four categories that might be involved in MEs and cause patient harm or injury. [5] Analgesics (opioid and none opioid) are prone for MEs because of the nature of the medication and variety of weightbase dosing ranges. [16] Little is known about the incidence of all types of MEs in pediatric population Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, off-label prescriptions are not necessarily incorrect, 6 and may even be appropriate in certain clinical situations provided there is no alternative treatment, and when the likely benefits outweigh the potential risks, 7 such as when conventional treatments are unable to achieve control of the disease. The potential advantages of off-label prescribing, apart from the probable benefit to the individual patient, are that new therapeutic uses may be described, and data on the efficacy and safety of the drug being used in new settings may be collected.…”
Section: Pimecrolimus 2 Yearsmentioning
confidence: 99%